3D finite element analysis of stress distribution on the shape of resected root-end or with/without bone graft of a maxillary premolar during endodontic microsurgery - Aein Mon; Mi-El Kim; Kee-Yeon Kum; Ho-Beom Kwon (Elsevier, 2024)
Background/purpose: Apical root resection pattern affects the stress distribution behavior in the apical region of the resected tooth. The purpose of the study was to compare the biomechanical responses of resected teeth between endodontic microsurgery (horizontal resection) and targeted endodontic microsurgery (round resection). Materials and methods: Five different models were developed. The basic model without resection (NR) was regarded as the control model, and the others involved: horizontal resection without bone grafting (HN), horizontal resection with bone grafting (HG), round resection without bone grafting (RN), and round resection with bone grafting (RG) models. A static load of 100 N was applied to the buccal and palatal cusps of all the teeth in a 30° oblique direction. The maximum von-Mises stress and tooth displacement values were analyzed and compared. Results: Both the HN and RN models exhibited lower stress distribution values on bone compared with the NR (control) model. Regarding maximum stress distribution at the root apex, the stress value of the RN model was slightly higher compared to the HN model, whereas the RG model displayed a slightly lower stress value in comparison with the HG model. For maximum tooth displacement value, there were no significant differences between the HN and RN models, as well as the HG and RG models. Conclusion: The round resection pattern had comparable stress distribution behaviors at the root apex and tooth displacement values with the horizontal resection pattern. Targeted endodontic microsurgery might provide better biomechanical response of the resected tooth after root-end resection.